Development of Balanced Whole System Value Measures for Inflammatory Bowel Disease Care in the IBD Qorus Collaborative Using a Modified Delphi Process. Issue 3 (25th May 2021) - Oliver, Brant J; Kennedy, Alice M; van Deen, Welmoed K; Weaver, S Alandra; Heller, Caren; Holthoff, Megan M; Bank, Jeffrey; Melmed, Gil Y; Siegel, Corey A; Nelson, Eugene C
Abstract: Background: The IBD Qorus Collaborative aims to reduce variation and increase the value of care for the adult inflammatory bowel disease (IBD) community. To evaluate the success of the collaborative, we aimed to develop a balanced set of outcome measures that reflect a multistakeholder view of value in IBD care. To achieve this, we used the Clinical Value Compass framework and engaged a mixed-stakeholder group to conduct a modified Delphi process. The end result was a 10-measure set to assess the value of IBD care. Method: The modified Delphi process included 3 iterative rounds of blinded voting and interactive webinar-style discussion. We recruited 18 participants for the Delphi panel, including clinicians, researchers, patients, Crohn's & Colitis Foundation staff, and payers. Participants first identified constructs to measure, then identified the tools to measure those constructs. A literature review and environmental scan of current measures in 4 domains were performed, and relevant measures were proposed for discussion and voting in each domain. Throughout the process, participants were invited to contribute additional measures. Conclusion: The modified Delphi process led to selection of 10 value measures across 4 domains: (1) patient experience; (2) functional status; (3) clinical status; and (4) health care costs and utilization. We have successfully completed a 3-stage modified Delphi process to develop a balanced set of value measures for adult IBD care. The value measure set expands upon prior efforts that have established quality measures for IBD care by adding cost and experience of care elements. This work positions IBD Qorus to better assess, study, improve, and demonstrate value at individual, system, and population levels and will inform and empower related research, improvement, and implementation efforts.